Sandbar Formation in the Mesjid River Estuary, Rupat Strait, Riau Province, Indonesia - Rifardi Rifardi; Yeeri Badrun (Faculty of Geography, Universitas Gadjah Mada, 2017)
At the aim to clarify the relationship between the sandbar formation and lithogeneous sediment discharges, the sedimentological aspects of the Mesjid River Estuary are revealed by various analysis. The samples of bottom surface sediments and the suspended sediment were collected at 50 stations in the estuary using grab and van dorm samplers. Oceanographic observation were also carried out at the stations. The Mesjid River Estuary receives lithogeneous sediments mainly from the Mesjid River’s drainage areas which play important role on the formation of sandbar which is shown by a belt-like area (0.5-1.0 m depth) in the area off the river mouth. The sandbar might become a sandbank in 20 to 40 years later. High suspended sediment up to 354.61 mg/l indicates the river mouth receives lithogeneous sediments. Total of 926 ton/day of the sediments supplied by the river are deposited 0.024 m/year into the area.